STUDI KEANEKARAGAMAN JENIS BURUNG DI KAWASAN HUTAN KOTA DESA KUWIL KABUPATEN MINAHASA UTARA - Rio Priyanto Saibi; Saroyo ., Saroyo; Hanny Hesky Pontororing (Universitas Sam Ratulangi, 2021)
Birds are one of the forest's ecosystem components which able to help in the forest's natural regeneration, with one of the bird's natural habitats being urban forests. This study aims to analyze the diversity and describe the bird's species in the Urban Forest habitat of the Kuwil Village of North Minahasa Regency. Data collection used survey methods with plots in form of 2 rectangular line transects with a length of 2000 m each and 20 m wide. Data collection is done 5 times. Based on the research, there were 10 species of birds with a diversity index of bird species as 1.98 which was in the medium category. The species found were Halcyon chloris, Corvus enca, Pycnonotus aurigaster, Oriolus chinensis, Gerygone sulphurea, Galliralus torquatus, Phaenicophaeus calyorhynchus, Eudynamys melanorhyncus, Geopelia striata, and Ducula aenea.